How masticatory function and periodontal disease relate to senile dementia - Yutaka Watanabe, PhD, DDS; Hirohiko Hirano, PhD, DDS; Kenji Matsushita, PhD, DDS (Elsevier, 2015)
This study reviews the research of dementia, a pathology for which numerous studies have found associations with masticatory function in the elderly. These issues are presently major problems in geriatric medical and welfare settings, and we discuss the prospects for future research into mastication. Dementia and masticatory function have been examined in a range of epidemiological and neuroscientific studies, and associations between the two have been reported. However, a causal relationship has not been satisfactorily established. Biochemical studies have also clarified the basis of the association between dementia and periodontal disease, but have not yet yielded sufficient evidence. Studies offering a high level of evidence, such as intervention studies and meta-analyses, are expected to be undertaken in this area in the future. Maintenance and recovery of masticatory function is of great importance with respect to achieving healthy longevity. Dental science will have considerable obligations and will have to take on an important role in this regard. For dental treatment to take on such important roles in the fields of health, medicine and welfare, it is necessary to provide information that will be understood not just by other medical and healthcare professionals, but also by the general public.